Impact of Community Self-Help Initiatives on the Attainment of Sustainable Development Goals 1 and 2 in Ikot Ekpene Senatorial District - Ironbar, V. E.; Ibok, E. O.; Okon, U. N. (Journal of Research in Adult and Continuing Education, 2025)
This study investigated the impact of community self-help initiatives on the attainment of Sustainable Development Goals 1 (no poverty) and 2 (zero hunger’) in Ikot Ekpene Senatorial District of Akwa Ibom State, Nigeria. Two research questions guided the study. Descriptive survey research design was adopted for this study with a sample of 728 respondents selected from the population of 72,099 members of the various registered community development associations in the study area. Both stratified and accidental sampling techniques were used. A validated questionnaire titled Community Self-Help Initiatives and the Attainment of Sustainable Development Goals One & Two (No Poverty & Zero Hunger) Questionnaire (CSHIASDGQ) was used to collect data for the study. The reliability of the instrument was done using Cronbach alpha reliability and result showed the reliability index range from 0.70 and 0.84. Descriptive statistical analysis such as mean, standard deviation, frequency, percentages and graphs were used to analyze data for the study. The results revealed that community road network and vocational skills training initiatives has a strong positive impact on the attainment of SDG 1 (No Poverty) and SDG 2 (Zero Hunger) in the study area. Based on the findings, it was recommended among others that government should prioritize the construction and maintenance of roads to enhance transportation, facilitate trade, and boost agricultural productivity. Better road networks will improve market access and create more economic opportunities.